Simultaneous unilateral thoracoscopic resection of bilateral pulmonary sequestration - Rui Guo; Sai Huang; Shisong Zhang; Huashan Zhao; Longfei Lv; Yunpeng Zhai (BMC, 2024)
Abstract Background Intra-lobar (ILS) and extra-lobar lung (ELS) sequestrations represent rare congenital lung malformations. Despite their benign nature, the lesions pose risks such as recurrent pulmonary infections, hemoptysis, congestive heart failure, and tumor development. Pulmonary sequestration (PS) typically manifests in two forms, ILS and ELS, with bilateral occurrence being exceptionally rare and mostly requiring bilateral thoracic surgery. Case presentation A 9-year-old child, who initially presented with bilateral lung lesions without respiratory symptoms, was diagnosed with PS following a chest computed tomography scan. The surgical approach was determined based on the absence of inflammation and the clear demarcation of the lesions from normal lung tissue, highlighted by a unique tissue connection between the ILS and ELS across the chest cavities. We used a novel method wherein the left ELS was successfully pulled into the right chest cavity and both sequestrations were concurrently resected. Postoperative recovery was smooth, with no complications or residual lesions. Conclusions Our findings highlight the importance of thorough preoperative planning with enhanced computed tomography. Simultaneous unilateral thoracoscopic surgery can be a viable, less invasive option for treating bilateral PS, offering benefits such as reduced recovery time and better cosmetic outcomes.